2009
DOI: 10.1007/s10592-009-9806-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly differentiated population structure of a Mangrove species, Bruguiera gymnorhiza (Rhizophoraceae) revealed by one nuclear GapCp and one chloroplast intergenic spacer trnF–trnL

Abstract: To evaluate the genetic diversity of a mangrove species and clarify the genetic structure of its populations, we studied nucleotide polymorphism in two DNA regions of Bruguiera gymnorhiza collected from the southern islands of Japan, Thailand, Malaysia, Indonesia, Micronesia, and India. The two DNA sequences were the chloroplast (cp) intergenic spacer between trnL and trnF genes (ca. 300 bp), and a part (ca. 550 bp) of the nuclear gene coding for glyceraldehyde-3-phosphate dehydrogenase (GapCp). Little polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…As previous research demonstrated varying influence of the Malay Peninsula on gene flow (inferred from genetic structure) [4], we tested the significance of the Malay Peninsula as a genetic barrier by using twelve populations (six from either side of the peninsula) from our dataset that represented both coasts of the peninsula. The EIO populations (west coast Malay Peninsula) were represented by MY1, MY2, TH1, TH2, MA1 and MA2.…”
Section: Nuclear Microsatellite Data Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…As previous research demonstrated varying influence of the Malay Peninsula on gene flow (inferred from genetic structure) [4], we tested the significance of the Malay Peninsula as a genetic barrier by using twelve populations (six from either side of the peninsula) from our dataset that represented both coasts of the peninsula. The EIO populations (west coast Malay Peninsula) were represented by MY1, MY2, TH1, TH2, MA1 and MA2.…”
Section: Nuclear Microsatellite Data Analysismentioning
confidence: 99%
“…Similarly in the IWP, the Malay Peninsula, which separates the East Indian Ocean (EIO) and South China Sea (SCS), was found to be a strong genetic barrier for many mangrove species. The genetic divide was thought to be caused by the geographic separation between populations in the Pacific Ocean from those in the Indian ocean that was imposed by the land mass during past glacial maxima [4]. In addition, mangroves from the IWP also exhibited phylogeographic congruency across species, whereby populations were genetically differentiated according to three subregions: the EIO, SCS and Northern Australia (NA), thus suggesting limited gene flow across these subregions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The species of the mangroves along the coast of the Chinese mainland differ from those of Taiwan (Becker 1922), Northeast Borneo (Parent 1935) and those of the southern part of the South China Sea, as shown in the present study. Differences in faunal composition between the Gulf of Thailand and the Andaman Sea is more trivial, since the composition of the mangrove flora on either side of the Thai-Malay Peninsula has been proven to be different (Ge & Sun 2001;Huang et al 2008;Minobe et al 2009;Liao et al 2009). We do not yet have information on the insect fauna in general.…”
Section: Discussionmentioning
confidence: 99%